Collocation of avian and mammal antibodies to develop a rapid and sensitive diagnostic tool for Russell's Vipers Snakebite - Lin, Jing-Hua; Lo, Che-Min; Chuang, Ssu-Han; Chiang, Chao-Hung; Wang, Sheng-Der; Lin, Tsung-Yi; Liao, Jiunn-Wang; Hung, Dong-Zong (PLoS neglected tropical diseases, 2020)
Russell's vipers (RVs) envenoming is an important public health issue in South-East Asia. Disseminated intravascular coagulopathy, systemic bleeding, hemolysis, and acute renal injury are obvious problems that develop in most cases, and neuromuscular junction blocks are an additional problem caused by western RV snakebite. The complex presentations usually are an obstacle to early diagnosis and antivenom administration. Here, we tried to produce highly specific antibodies in goose yolks for use in a paper-based microfluidic diagnostic kit, immunochromatographic test of viper (ICT-Viper), to distinguish RVs from other vipers and even cobra snakebite in Asia. We used indirect ELISA to monitor specific goose IgY production and western blotting to illustrate the interaction of avian or mammal antibody with venom proteins. The ICT-Viper was tested not only in prepared samples but also in stored patient serum to demonstrate its preliminary efficacy. The results revealed that specific anti-Daboia russelii IgY could be raised in goose eggs effectively without inducing adverse effects. When it was collocated with horse anti-Daboia siamensis antibody, which broadly reacted with most of the venom proteins of both types of Russell's viper, the false cross-reactivity was reduced, and the test showed good performance. The limit of detection was reduced to 10 ng/ml in vitro, and the test showed good detection ability in clinical snake envenoming case samples. The ICT-Viper performed well and could be combined with a cobra venom detection kit (ICT-Cobra) to create a multiple detection strip (ICT-VC), which broadens its applications while maintaining its detection ability for snake envenomation identification. Nonetheless, the use of the ICT-Viper in the South-East Asia region is pending additional laboratory and field investigations and regional collaboration. We believe that the development of this practical diagnostic tool marks the beginning of positive efforts to face the global snakebite issue.